Sistem Informasi Inventori Berbasis Website pada Bengkel Mspeed Jakarta - Maliki Mangasi; Mira Ziveria (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Inventory system is a system that used to enter inventory data into a storage or database, the purpose is to minimizing the occurrence of errors in incoming goods, outgoing goods and making reports based on existing data. This research was conducted to build a system inventory of workshops that aim to facilitate users in controlling inventory. This research uses a prototype method by building a website based inventory system. In the process of collecting data, researchers use interviews and observations. This research resulted in website based inventory system that can assist users in carrying out inventory activities at the workshop.